Study on water quality simulation and dynamic water environment capacity of Helan County section of the third drainage ditch in Ningxia - Yang, Cheng; Zheng, Lanxiang; Zhang, Zunyang; Feng, Minquan (Frontiers in Ecology and Evolution, 2022)
The Helan section of the third drainage ditch in Ningxia is selected as the research object, and its water environmental capacity is analyzed; The Daily discharge and water level are calculated according to the measured data; Then the daily concentration values of the main water quality indexes are simulated by one-dimensional hydrodynamic water quality mathematical model; Finally, the dynamic water environment capacity is calculated. The results show that from May to October 2020, the main water quality indicators exceeding the standard in Helan section of the third drainage ditch were total nitrogen and five-day biochemical oxygen demand. Their water environmental capacity was −11.8744 t and −67.1173 t, respectively. Chemical oxygen demand and total phosphorus exceeded the standard severely in some months. There are problems of eutrophication and high organic content in drainage ditches. The primary pollution sources are aquaculture wastewater form fishery, farmland drainage, seasonal flood, and domestic sewage. It is suggested to take preventive measures such as source control, process blocking, and end treatment.